Subjektivni obseg arbitražnega sporazuma - Gvardjančič, Minu A. (Podjetje in delo, 2021)
The article examines the subjective scope of an arbitration agreement, which determines the subjects that are bound by an arbitration agreement. Due to the principle of relativity of contractual relations (validity inter partes), generally there is a rule that an arbitration agreement can only bind the parties to it, and not third parties. Nevertheless, it often happens in practice that the parties to arbitration proceedings are also persons who have not concluded an arbitration agreement (for example in case of surety) or who have signed the arbitration agreement on behalf of someone else (for example a legal representative on behalf of a legal entity). Such examples also occur in cases of assignment or transfer of debt and in legal succession. Moreover, situations where one party is closely related to another party or contract, and that party is not a direct party to a contract (as it is the case of concluding contracts among group of companies), should also not to be overlooked. Today, therefore, the question of whether an arbitration agreement can also bind third parties is no longer as important, as it is clear that the answer is positive; however, there is no unanimous solution regarding the conditions under which an arbitration agreement may bind (also) non-signatories. Arbitral and judicial case law is not uniform in this regard, while international and national arbitration sources mostly remain silent on this issue.
Keywords: arbitration agreement; arbitration law; arbitražni sporazum; arbitražno pravo; conclusion of arbitration agreement; consent; nepodpisniki; non-signatories; pisna oblika; sklenitev arbitražnega sporazuma; soglasje; subjective scope; subjektivni obseg; written form